2018
DOI: 10.1002/solr.201800156
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Mechanism of an RbF Post Deposition Treatment in CIGS Thin Film Solar Cells

Abstract: The impact of a rubidium fluoride post deposition treatment (RbF-PDT) on the material and device properties of Cu(In,Ga)Se 2 (CIGS) thin films and corresponding solar cells is investigated. The structure and device properties of CIGS with different PDT duration are compared. With longer PDT duration, which equals a higher amount of RbF deposited on the CIGS absorber layer, a clear trade-off is observed between increasing open-circuitvoltage (V OC ) and decreasing fill factor (FF). An optimum of the PDT duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(126 citation statements)
references
References 49 publications
15
109
2
Order By: Relevance
“…This high performance was achieved by incorporating KF, RbF, or CsF into the absorber layer via PDT. Regarding the effects of alkali fluoride PDT on device parameters, an increase in the open‐circuit voltage ( V oc ) has been observed consistently, whereas short‐circuit current ( J sc ) and fill factor (FF) present an inconsistent trend in different contributions . For the context of this work, we note that some publications have reported the presence of a barrier for the bucking and/or photo current, resulting for instance in a rollover of the current–voltage ( J–V ) characteristics or a crossover between dark and light J–V curves after PDT …”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…This high performance was achieved by incorporating KF, RbF, or CsF into the absorber layer via PDT. Regarding the effects of alkali fluoride PDT on device parameters, an increase in the open‐circuit voltage ( V oc ) has been observed consistently, whereas short‐circuit current ( J sc ) and fill factor (FF) present an inconsistent trend in different contributions . For the context of this work, we note that some publications have reported the presence of a barrier for the bucking and/or photo current, resulting for instance in a rollover of the current–voltage ( J–V ) characteristics or a crossover between dark and light J–V curves after PDT …”
Section: Introductionmentioning
confidence: 68%
“…In addition, studies demonstrated that if Na is present at the heterointerface between ZnO and CIGS in superstrate solar cells, the high density of deep acceptor states at the heterointerface lowers the FF, and therefore the device performance . Notwithstanding the different preparation sequences in our substrate cells, a similar situation may nevertheless arise . Thus, introducing acceptor states at the CdS/ZnO interface induced by Rb migration could explain some of the nonidealities presented in RbF‐treated samples within the scope of our numerical simulations.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Concerning absorber elements, in both cases, Cu depletion and In enrichment are observed at the grain boundary, the latter being slightly more pronounced when the RbF‐PDT is applied. Accumulation of Rb at grain boundaries and dislocation cores has also been observed by TEM and X‐ray fluorescence investigations of RbF‐treated Cu(In,Ga)Se 2 absorbers and has been proposed as the cause of reduced bulk recombination …”
Section: Effects Of Post‐deposition Treatment With Heavy Alkalismentioning
confidence: 81%